Prevalence of Bunostomum trigonocephalum infection in sheep and goats in Madhya Pradesh - Khare, Ravi Kumar; Dixit, AK; Kumar, R; Das, G; Bhinsara, D; Ghosh, Subhamoy; Singh, Rohit; Chandra, D; Sankar, M (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
work is properly cited. Copyright @: 2018 by authors and SVSBT. Introduction Abstract Bunostomum trigonocephalum is one of the neglected and highly pathogenic nematodes of small ruminants. The accurate prevalence of bunostomosis is under estimated because it is morphologically indistinguishable with another blood sucking nematode, Gaigeria pachyscelis. The prime objective of the present study was to estimate the prevalence of B.trigonocephalum in different region of Madhya Pradesh and reinforce identification and differentiation characters between B.trigonocephalum and G. pachyscelis. A total of 52 intestines were screened from different places of Madhya Pradesh and B. trigonocephalum and G. pachyscelis were identified morphologically. The overall prevalence of B.trigonocephalum was 30.76% in Madhya Pradesh. The highest prevalence (85.71 %) was found in the Baghelkhand region (Rewa) is followed by Mahakoshal region (Jabalpur) (83.33%) and Vindhyanchal plateau (Bhopal) (66.66%). Beside B.trigonocephalum, G. pachyscelis was also prevalent (57.14%) in Rewa. The characteristic morphological differences between B.trigonocephalum and G. pachyscelis were discussed. and reported from different states of our country Gastrointestinal nematode infection in sheep and goats is ubiquitous and severely affects small ruminants production, worldwide. In India, the income from small ruminants is major source to the middle and marginal farmers (Bandyopadhyay, 1999). However, gastrointestinal parasitism led by strongyles has detrimental effects on production by reduction in growth and development, and mortality in growing animals. Among strongyles, Haemonchus contortus, Trichostrongylus colubriformis and Oesophagostomum columbianum are well studied